ASSESSMENT OF TRACER STUDY REPORT AS AN EVALUATION OF DEVELOPMENT OF THE ISLAMIC BANKING STUDY PROGRAM AT UNIVERSITAS MUHAMMADIYAH PROF DR HAMKA - Nur Melinda Lestari; Andi Amri (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
Tracer study is an alumni survey carried out by universities to explore information about the journey of their graduates, starting from the graduates completing their education in college until with the timing of the conduct of the survey. The purpose of the tracer study is to find out the quality of graduates produced by universities, as well as extract further information to alumni, related to career choices that are carried out as input for the improvement of the Sharia Banking study program at the University of Muhammadiyah Prof. DR HAMKA in the future. The stages passed, namely starting from the development of concepts and instruments, continued with data collection, then analysis of data that has been collected, preparation of reports on the results of tracer studies, and finally making scientific articles that can be read by academics. The study began in January to August 2022. The search was carried out to alumni of the Sharia Banking department of the Faculty of Islamic Religion, University of Muhammadiyah Prof. DR HAMKA who graduated in 2020, 2021, and 2022. The results showed that the Islamic Banking alumni who succeeded in filling in were 72 people, of which 16 were men and 56 women. The source of funds in financing college during alumni's studies comes from personal/family expenses of 93%. The learning method that is often carried out emphasizes the use of lecture, praticum, and discussion methods. In addition, for alumni satisfaction with leaders, lecturers, and educational staff / employees, the average is in a state of satisfaction. This also has an impact on graduates of the Islamic Banking study program who easily and quickly get an appropriate and ideal job, because it is also supported by the Al Islam program Kemuhammadiyahan.